M. Akmulla's Traditions In Kasim Bikkulov's Educational Poetry - Nurieva, Liliya F.; Sayfulina, Flera S.; Gilazov, Tagir Sh; Alkaya, Ercan (Modern Journal Language Teaching Methods, 2018)
The article is devoted to the analysis of the poetic works by Kassim Bikkulov, the poet and the writer of the early twentieth century in the context of Tatar literature educational traditions. The literary heritage of the writer-educator makes about a dozen realistic stories; short stories, poems and scientific and educational records of informative nature, devoted to natural phenomena and included in the books for reading. The research object of this article is educational poems aimed at the development of morality among young readers, their engagement to enlightenment, the acquiring of secular knowledge included in the collection of works reprinted for the first time in 100 years (2016). The aim of the work is the study and the introduction of the poems by Kasim Bikkulov to the scientific circulation, which are considered by the authors of this article in the framework of Tatar literature educational traditions, also in a comparative perspective with the works of the famous Tatar poet of the second half of the XIXth century - Miftahutdin Akmullah. We used analytical, comparative, cultural and historical research methods, as well as a hermeneutic approach to the analysis of the works. The novelty and the relevance of the work is explained by a poor study of the writer-educator poetic heritage, a clergyman, whose works were undeservedly forgotten during the years of the totalitarian regime. In the framework of educational poetry, dozens of poems by Kasim Bikkulov were analyzed, they performed the comparative analysis of the works by the author under study with M. Akmulla's poetry. M. Akmulla is the enlightener. The study makes it possible to draw the conclusions that the poetry of the analyzed poet K. Bikkulov, in contrast to his prosaic heritage, which is more considered in terms of critical realism, relates to educational literature.
Keywords: Tatar literature; K. Bikku lov; literary process; literary heritage; enlightenment